THE IMPACT OF ROLE CONFLICT, AMBIGUITY, AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE MEDIATED BY AFFECTIVE COMMITMENT (Studi Pada PT. Gratia Husada Farma Karangjati) - Diah Puji Larasati,; Efriyani Sumastuti,; Ika Indriasari, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Abstract This study explores the influence of role conflict, ambiguity, and career development on employee performance at PT. Gratia Husada Farma Karangjati, with affective commitment as a mediating factor. A quantitative method was used, gathering data from 100 respondents through simple random sampling. The data were analyzed using multiple linear regression and the Sobel test. The results indicate that role conflict and ambiguity negatively impact employee performance, while career development has a positive effect. Additionally, affective commitment enhances employee performance and mediates the relationship between ambiguity and career development with employee performance, but it does not mediate the effect of role conflict. These findings underscore the importance of addressing ambiguity and promoting career development to improve employee performance through increased affective commitment. The study offers valuable insights into the role of affective commitment in fostering employee performance and highlights the need for companies to focus on employee development and emotional engagement. Keywords: role conflict, ambiguity, career development, affective commitment, employee performance